The Role of Store Brand Spillover in a Retailer’s Category Management Strategy - Alan, Yasin; Kurtuluş, Mümin; Wang, Chunlin (Manufacturing and Service Operations Management, 2019)
Problem definition: We study a retailer’s category management strategy and interactions with its supply chain partners in a setting in which increasing the store brand (SB) market share in a focal category improves the retailer’s overall profitability by creating demand spillover to other categories. Academic/practical relevance: Unlike most category management research, which focuses on category profit maximization, our research incorporates SB spillover observed in practice into the retailer’s decision making. Methodology: We analyze a game-theoretic model with one retailer, one high-quality national brand (NB) manufacturer, and one low-quality NB manufacturer. The retailer selects the assortment and sets the retail prices, and the NB manufacturers set their wholesale prices. We formulate the retailer’s objective function as a weighted sum of category profit and SB market share, where the weight assigned to the SB market share captures the degree of SB spillover. Results: First, overlooking SB spillover can result in suboptimal assortment and pricing decisions, leading to financial losses for the retailer. The retailer incurs the largest losses when it fails to adjust its assortment to take SB spillover into account, whereas its losses are relatively small when it carries the right assortment but fails to adjust its prices. Second, taking SB spillover into account decreases the retailer’s category profit when the degree of SB spillover is high. However, a low degree of SB spillover may enable the retailer to simultaneously increase its category profit and SB market share. Third, SB spillover is never beneficial for the low-quality NB but may increase the high-quality NB’s profit when the retailer removes the low-quality NB from its assortment. Managerial implications: Our study sheds light on how SB spillover affects the retailer’s assortment and pricing decisions and demonstrates the impact of such decisions on the retailer, the focal category, and the NBs.